Age Related Changes of Bone Marrow Cellularity in Medicolegal Autopsies - Akyıldız, Elif Ülker; Akı, Hilal; Çelik, Safa (The Bulletin of Legal Medicine, 2003)
Knowledge of the normal variations with aging of the bone marrow cellularity is essential for the interpretation of bone marrow features. We performed a histological study using biopsy samples of bone marrow obtained from medicolegal autopsies ranging from first to eighth decades. As a matter of increasing age, an increasing fat tissue fraction was observed.Key words: Bone marrow, cellularity, aging.
Keywords: bone marrow; cellularity; aging